ODAN'S CV TRAVEL MARKETING PATTERNS IN INCREASING SERVICE QUALITY TO TOURISTS IN BATUBARA DISTRICT - Muhammad Rafli Luthfi Luthfi; Muhammad Alfikri (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This study aims to find out how CV Travel Odan's marketing pattern improves the quality of service to tourists in Batubara Regency. As a theoretical basis in analyzing the problems in this qualitative research, theories about marketing communications and tourists are used, so that researchers are required to obtain data and information by conducting in-depth interviews and observations. This research uses a qualitative approach that is descriptive. The informants in the study were CV Travel Odan workers and tourists who used CV Travel Odan's services. The data collection techniques used were interviews, observation and documentation, using a phenomenological study approach, namely researchers trying to find the meaning of marketing communication phenomena used by CV Travel Odan. The data analysis used by the researcher is descriptive analysis, which summarizes all the data that has been collected from the interviews. The results of this study indicate that to improve service quality CV Travel Odan will increase consumer confidence by conducting persuasive communication, repositioning strategies and strategies to provide extra services for tourists. Keywords: Marketing Patterns, Service Quality, Tourists